Retention of Human iPSC-Derived or Primary Cells Following Xenotransplantation into Rat Immune-Privileged Sites - Thomas Später; Giselle Kaneda; Melissa Chavez; Julia Sheyn; Jacob Wechsler; Victoria Yu; Patricia Del Rio; Dave Huang; Melodie Metzger; Wafa Tawackoli; Dmitriy Sheyn (Bioengineering, 2023)
In regenerative medicine, experimental animal models are commonly used to study potential effects of human cells as therapeutic candidates. Although some studies describe certain cells, such as mesenchymal stromal cells (MSC) or human primary cells, as hypoimmunogenic and therefore unable to trigger strong inflammatory host responses, other studies report antibody formation and immune rejection following xenotransplantation. Accordingly, the goal of our study was to test the cellular retention and survival of human-induced pluripotent stem cell (iPSCs)-derived MSCs (iMSCs) and primary nucleus pulposus cells (NPCs) following their xenotransplantation into immune-privileged knee joints (14 days) and intervertebral discs (IVD; 7 days) of immunocompromised Nude and immunocompetent Sprague Dawley (SD) rats. At the end of both experiments, we could demonstrate that both rat types revealed comparably low levels of systemic IL-6 and IgM inflammation markers, as assessed via ELISA. Furthermore, the number of recovered cells was with no significant difference between both rat types. Conclusively, our results show that xenogeneic injection of human iMSC and NPC into immunoprivileged knee and IVD sites did not lead to an elevated inflammatory response in immunocompetent rats when compared to immunocompromised rats. Hence, immunocompetent rats represent suitable animals for xenotransplantation studies targeting immunoprivileged sites.